Converging biofabrication and organoid technologies: the next frontier in hepatic and intestinal tissue engineering?. (6th March 2017) - Schneeberger, Kerstin; Spee, Bart; Costa, Pedro; Sachs, Norman; Clevers, Hans; Malda, Jos
Abstract: Adult tissue stem cells can form self-organizing 3D organoids in vitro . Organoids resemble small units of their organ of origin and have great potential for tissue engineering, as well as models of disease. However, current culture technology limits the size, architecture and complexity of organoids. Here, we review the establishment of intestinal and hepatic organoids and discuss how the convergence of organoids and biofabrication technologies can help overcome current limitations, and thereby further advance the translational application of organoids in tissue engineering and regenerative medicine.